DEVELOPMENT OF THE TECHNOLOGY OF A HIGH-PROTEIN FERMENTED DRINK ON A PLANT BASIS - Novik, Anna; Lapytska , Nadiya; Lystopad, Tamara; Boychenko, Polina; Savchenko , Alina (Biota. Human. Technology, 2022)
The article presents the results of the study of plant-based substitutes for dairy products. It is shown that yogurts based on these starters have higher sensory indicators compared to traditional drinks. The purpose of the article is the scientific substantiation and development of the optimal formulation and production technology of a high-protein fermented beverage based on chickpeas and flax protein. Methodology. Microbiological, physicochemical and sensorial research methods were used. Processing of the results was carried out using MS Excel databases. The scientific novelty is that during the development of the concept of creating technologies for new fermented drinks, in which the protein content is increased and the amino acid composition is improved by adding chickpeas and flax protein. Conclusions. The prospect of using fermented beverages made on a plant basis has been proven. It was established that the developed drink samples were based on a set of indicators (amino acid composition and soon, potential biological value of protein, utilitarian coefficient of amino acid composition of protein, indicator of "excess content" of essential amino acids, ratio of fatty acids С18:2:С18:1 and С18:2:С18:3) are characterized by high biological value of proteins and lipids. The recipe composition of a high-protein fermented chickpea-linseed drink is substantiated and the optimal ratio of water: vegetable protein preparations in the recipe composition is determined.